DISCURSIVE MEANS OF PRAGMATIC INFLUENCE IN THE SERIES OF GRAPHIC NOVELS "MAUS" BY ART SPIEGELMAN - Michael Kamensky (Гуманитарные и юридические исследования)
The article contains the results of research of explicit and implicit discursive means of exerting pragmatic impact on recipient in graphic novel as a speciic genre of the discourse of iction based on a sequentially organized creolized text. The research was conducted on the basis of Art Spiegelman's series of graphic novels "Maus" which are a form of autobiographical narrative about the author's father who is a survivor of the holocaust and the Aushwitz concentration camp during World War II. The authors focus on the results of analyzing the complex pragmatic context of the graphic novel that is based on the informational-descriptive, functional-dynamic, structural-compositional and dispositional-evaluative subcontexts. As a result of the analysis the authors determined the peculiar features of the graphical novel as a communicatively oriented form of literature aimed at conveying the author's opinion and feelings through language signs; determined the role of the visual component of the graphical novel in forming the pragmatic potential of the novel through the images presented on the sequentially organized panels; proved that the images in the graphical novel are an instrument of portraying the author's world and a mechanism of provoking the reader's emotional response necessary to believe the author's narrative.